A prediction model for periodontal disease: modelling and validation from a National Survey of 4061 Taiwanese adults. (22nd April 2015) - Lai, Hongmin; Su, Chiu‐Wen; Yen, Amy Ming‐Fang; Chiu, Sherry Yueh‐Hsia; Fann, Jean Ching‐Yuan; Wu, Wendy Yi‐Ying; Chuang, Shu‐Lin; Liu, Hsing‐Chih; Chen, Hsiu‐Hsi; Chen, Li‐Sheng
Abstract Aims The aim of this study was to predict periodontal disease (PD) with demographical features, oral health behaviour, and clinical correlates based on a national survey of periodontal disease in Taiwan. Materials and Methods A total of 4061 subjects who were enrolled in a cross‐sectional nationwide survey on periodontal conditions of residents aged 18 years or older in Taiwan between 2007 and 2008 were included. The community periodontal index (CPI) was used to measure the periodontal status at the subject and sextant levels. Information on demographical features and other relevant predictive factors for PD was collected using a questionnaire. Results In our study population, 56.2% of subjects had CPI grades ≥3. Periodontitis, as defined by CPI ≥3, was best predicted by a model including age, gender, education, brushing frequency, mobile teeth, gingival bleeding, smoking, and BMI. The area under the curve (AUC) for the final prediction model was 0.712 (0.690–0.734). The AUC was 0.702 (0.665–0.740) according to cross‐validation. Conclusions A prediction model for PD using information obtained from questionnaires was developed. The feasibility of its application to risk stratification of PD should be considered with regard to community‐based screening for asymptomatic PD.